Conjugal violence and emotional dependence in women victims of abuse in Peru reported in the first quarter of 2021 - Radas Barbié , Doris Luz (2022)
The present study aims to identify the mistreatment that women are victims by their partner in Peru from those reported within the first quarter of 2021, carried out through an exploration of different investigations, managing to identify that the violence exerted on The women have not stopped, quite to the contrary, the cases are increasing and unfortunately each time they are identified; Through the information found, it is possible to identify that the victims have more than once returned to their aggressor, who is identified as their partner.